Awareness and attitudes of pregnant women concerning genetic disorders and pregnancy termination in northeastern Iran - Nafiseh Todarbary; Abouzar Irandegani; Mojtaba Meshkat; Aida Gholoobi; Tayebeh Hamzehloei (Egyptian Journal of Medical Human Genetics)
Abstract Background Genetic disorders are common in the Eastern Mediterranean region due to the high prevalence of consanguineous marriages. This study explores the awareness and attitudes of pregnant women in Mashhad, the biggest city in northeastern Iran, toward genetic disorders and the decision-making process regarding pregnancy termination. This study included 297 pregnant women across five hospitals in Mashhad, Iran. They filled out a checklist comprised of demographic data and questions about abortion decisions facing a child with various genetic disorders or undesired gender. Results The majority (75%) agreed with abortion in cases of anencephaly, while only 19% accepted it for undesired gender. Education level was associated with abortion agreement for various conditions, including cleft lip or palate, Alzheimer’s disease, Turner syndrome, cystic fibrosis, phenylketonuria, Huntington’s disease, autism, fragile X syndrome, and epilepsy. Additionally, the number of children was correlated with congenital blindness, Duchenne muscular dystrophy, autism, Proteus syndrome, Klinefelter syndrome, anencephaly, mental retardation (MR), quadriplegia, and severe learning disability and mental health (LDMH). Age was associated with conditions such as epilepsy, congenital blindness, schizophrenia, and severe LDMH. Furthermore, a history of anomalies in previous pregnancies was linked to Klinefelter syndrome, Turner syndrome, dwarfism, and quadriplegia. The number of pregnancies was also correlated with severe LDMH, dwarfism, and Klinefelter syndrome, while job status was related to epilepsy, Alzheimer’s disease, and dwarfism. Conclusion The findings emphasize the importance of comprehensive genetic counseling, informed decision-making in prenatal care, advocating for policy reviews, and culturally sensitive guidelines in Iran.